Psychological pressures and its correlation with attention skills in football referees, before and during competition - TISMOKA, Arezki (Journal of Human Sciences, 2020)
Through this study entitled: Psychological Pressures and Its Correlation with Attention Skills in Football Referees, before and during the competition, we split our study into two major parts, the first was to reser and the second was reserved for field study, where we followed the methodological and scientific steps required After the application of the tests in question, following methodological and scientific steps and after analysis and discussion of the results obtained through the investigative means previously cited and applied on our population of investigations that are the referees of football , our study resulted in the following main result: the main results  sources of pressure among referees are players and supporters and to a lesser degree of factors related to the security technical and administrative staff of clubs that have their turns exert pressure on the referee this study showed that there is also a correlation between the pressures and the level of attention of arbitrators (experience factors) which prevents     most of them from being more profitable.